Epidemiology and outcome of antimicrobial resistance to gram‐negative pathogens in bacteriuric kidney transplant recipients. Issue 4 (3rd July 2017) - Delmas‐Frenette, Catherine; Dorais, Marc; Tavares‐Brum, Alexandre; Frenette, Charles; Yang, Bing; Medani, Samar; Duclos, Alain; Rouleau, Danielle; Mawad, Habib; Barama, Azemi; Cardinal, Heloise
Abstract: Background: In kidney transplant recipients, episodes of bacteriuria are often treated regardless of the presence of symptoms because of the lack of clear treatment guidelines suggesting otherwise. This practice may lead to the development of antimicrobial resistance. Our aim was to determine the incidence, determinants, and impact of antimicrobial resistance in kidney transplant recipients with gram‐negative bacteriuria. Method: We conducted a single‐center, retrospective cohort study in patients who underwent kidney transplantation between January 2008 and June 2013. To identify risk factors for the development of resistance, we used a logistic regression model with generalized estimating equations to account for within‐subject correlation. Results: Among the 318 patients who underwent kidney transplantation during the study period, 147 patients developed 555 gram‐negative episodes of bacteriuria. Resistance to trimethoprim‐sulfamethoxazole and quinolones, and production of extended‐spectrum β‐lactamase (ESBL) occurred in 52%, 21%, and 5% of isolated microorganisms, respectively. An increased risk of resistance to quinolones and production of ESBL were associated with concomitant diabetes (odds ratio [OR]: 2.29, 95% confidence interval [CI]: 1.11‐4.74), the first year post transplantation (OR: 2.88, 95% CI: 1.36‐6.09), and antibiotic treatment in the previous 6 months (OR: 3.36, 95% CI: 1.66‐6.81). This resistance profile was also associated with the presence of symptoms, a longer duration of antibiotic treatment, and a higher rate of hospitalization. Conclusion: Antimicrobial resistance to quinolones and production of ESBL were commonly seen, and were shown to demonstrate an adverse impact on outcomes in kidney transplant recipients with gram‐negative bacteriuria. The decision on treatment for asymptomatic bacteriuria should be made with caution, given the potential for the selection of resistant strains.